2020
DOI: 10.3389/fphys.2020.00383
|View full text |Cite
|
Sign up to set email alerts
|

DI-5-CUFFS: Venoconstrictive Thigh Cuffs Limit Body Fluid Changes but Not Orthostatic Intolerance Induced by a 5-Day Dry Immersion

Abstract: Venoconstrictive thigh cuffs are used by cosmonauts to ameliorate symptoms associated with cephalad fluid shift. A ground simulation of microgravity, using the dry immersion (DI) model, was performed to assess the effects of thigh cuffs on body fluid changes and dynamics, as well as on cardiovascular deconditioning. Eighteen healthy men (25-43 years), randomly divided into two groups, (1) control group or (2) group with thigh cuffs worn 10 h/day, underwent 5-day DI. Cardiovascular responses to orthostatic chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 17 publications
7
18
0
Order By: Relevance
“…In a recent report, acute use of VTC during a 15 • tilt reversed tilt-induced increased IOP and subfoveal choroidal thickness (Balasubramanian et al, 2018). In this study, VTC is likely to tend to limit the reduction in IOP by preventing hypovolemia (previously demonstrated in this same study by Robin et al, 2020) thus diminishing ocular dehydration.…”
Section: No Effect Of DI On Iopsupporting
confidence: 66%
See 2 more Smart Citations
“…In a recent report, acute use of VTC during a 15 • tilt reversed tilt-induced increased IOP and subfoveal choroidal thickness (Balasubramanian et al, 2018). In this study, VTC is likely to tend to limit the reduction in IOP by preventing hypovolemia (previously demonstrated in this same study by Robin et al, 2020) thus diminishing ocular dehydration.…”
Section: No Effect Of DI On Iopsupporting
confidence: 66%
“…VTC have already been tested during short-term bed rest studies. Although their daily use proved their efficiency to limit hypovolemia and/or baroreflex impairment, VTC failed to prevent orthostatic intolerance (Arbeille et al, 1999;Custaud et al, 2000;Millet et al, 2000;Pavy-Le Traon et al, 2001;Robin et al, 2020); however, little is known about the impact of mechanical countermeasures on ocular changes. This study shows that VTC failed to prevent the increase in RNFLT in the temporal quadrant induced by DI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol did not include an assessment of post-biopsy pain, but no speci c events were reported during the muscle biopsies. The questionnaires on back pain and general discomfort only elicited signi cantly higher scores than in the pre-immersion period during the rst two days of immersion for both groups [35]. We believe that the most likely explanation for the increased CBF in the left thalamus at post-DI is the sensory stimulus generated by the muscle biopsy in the right thigh, the day before the brain SPECT.…”
Section: Discussionmentioning
confidence: 75%
“…According to the authors, the prolonged vasoconstriction and these histological changes could be responsible for an increase in CVR, thus contributing to the decrease in CBF [15]. During DI5-CUFFS, Robin et al observed a decrease in plasma volume across the 5 days [35]. Likewise, during 3-day DI, Ogoh et al demonstrated a correlation between the decrease in plasma volume and the decrease in blood ow velocity and conductance in the internal carotid artery [25], suggesting that the loss of plasma volume also contributes to the vasoconstriction of cerebral arteries.…”
Section: Discussionmentioning
confidence: 99%